Formulation, characterization, and evaluation of curcumin-loaded ginger-derived nanovesicles for anti-colitis activity - Shengjie Huang; Min Zhang; Xiaoge Li; Jierong Pei; Zhirong Zhou; Peng Lei; Meng Wang; Peng Zhang; Heshui Yu; Guanwei Fan; Lifeng Han; Haiyang Yu; et al. (Journal of Pharmaceutical Analysis)
Plant-derived nanovesicles have gained attention given their similarity to mammalian exosomes and advantages such as low cost, sustainability, and tissue targeting. Thus, they hold promise for disease treatment and drug delivery. In this study, we proposed a time-efficient method, PEG 8000 combined with sucrose density gradient centrifugation to prepare ginger-derived nanovesicles (GDNVs). Subsequently, curcumin (CUR) was loaded onto GDNV by ultrasonic incubation. The optimum conditions for ginger-derived nanovesicles loaded with curcumin (CG) were ultrasound time of 3 min, a carrier-to-drug ratio (GDNV:CUR) of 1:1. The study achieved a high loading capacity (94.027% ± 0.094%) and encapsulation efficiency (89.300% ± 0.344%). Finally, the drugs' in vivo distribution and anti-colitis activity were investigated in mice. CG was primarily distributed in the colon after oral administration. Compared to CUR and GDNV, CG was superior in improving disease activity, colon length, liver and spleen coefficients, myeloperoxidase activity, and biochemical factor levels in ulcerative colitis (UC) mice. In addition, CG plays a protective role against UC by modulating serum metabolite levels and gut flora. In summary, our study demonstrated that GDNV can be used for CUR delivery with enhanced therapeutic potential.